Dentists' Mobility in Thai Oral Health Service System during 1975-2005 - วิชชาวุธ, โกเมศ; ผลดีเยี่ยม, สุณี; สุคันวรานิล, สุพรรณี; เล็กสมบูรณ์, ดวงใจ; บุษราคัมรุหะ, จารุวัฒน์; วงค์คงคาเทพ, สุณี (Thai Dental Public Health Journal, 2008)
The purpose of this study was to analyse the baseline data for formulate the strategy for sustaining dentists in urban area. Topics focus on distribution workplace, salary per month, working time per week, duration before post-graduate studying, government (public) working period before resign, and turnover factors. The main study conducted by questionnaire and some interviews via telephone. Data collected during November 2006 - January 2007. 50.0% Sampling of graduated dentists in the year 1975, 1980, 1985, 1990, 1995, 1997, 1999, 2001, 2003, 2004 and 2005. Results shown that 51.3% dentists are working in hometown. Public salary ratio compare to private paid equal to 20.6 - 36.8 % and increase to be 40.9 - 59.7 after incentive payment added. Average working period between public and private dentist are relatively the same. New graduated dentists are likely to further education earlier than the previous dentists. In addition, trend showed that the newer dentists have more and fasting resign from public sector. Decision factors are hometown, family and continuing education.